Capital Market Instruments to Mobilize Institutional Investors to Infrastructure and SME Financing in Emerging Market Economies : Report for the G20 - World Bank Group (World Bank, Washington, DC; International Monetary Fund, Washington, DC; and OECD, Paris, 2015)
This report seeks to identify key capital markets instruments that can help mobilize institutional investors to infrastructure and small and medium enterprises (SME) financing in emerging market economies (EMEs). EMEs face financing gaps in infrastructure and SMEs that if not addressed can stifle growth and affect shared prosperity. This report is structured as follows: this section explains the objective of this report and the scope of the work undertaken. Section two provides an overview of the size and importance of institutional investors in EMEs and their current portfolio allocation. Sections three and four analyze key capital markets instruments that might help to mobilize institutional investors in EMEs to infrastructure and SME financing, and their current use in AEs and EMEs. Section five explains the challenges affecting the development of capital markets instruments in EMEs. Section six provides an overview of the role of governments and multilateral development banks (MDBs). Section seven draws conclusions and offer recommendations about actions that EMEs will need to undertake to mobilize institutional investors to infrastructure and SME financing.